Effect of degree of substitution of carboxyl groups on cross-linking of carboxymethyl starch - Pant, Bhoj Raj; Upadhyaya, Jitendra (Scientific World, 2022)
Cross-linked carboxymethyl starch of different degrees of substitution-DS (DS, 0.14, and 0.49) was synthesized and investigated the effect of DS on cross-linking of starch derivatives. Native corn starch was first carboxymethylated in an alkaline condition of the alcoholic medium using sodium chloroacetate as a carboxymethylating agent. The aqueous Carboxy Methyl Starch (CMS) solutions (15 and 50%, w/w) were then irradiated by electron beam (EB) radiations at 1, 2, 3, 5, 10, 20, and 50 kGy dosages and underwent radiation cross-linking, resulting in a Cross-linked Carboxymethyl Starch (CCMS). The gel content to be estimated in the CCMS of different DS (0.14 and .049) with 50% (w/w) CMS was 1.3 and 19.2%. These are the maximum degrees of cross-link achieved with 50% (w/w) aqueous CMS irradiated at 5 and 2 kGy dosages. Our results showed that the cross-linking of CMS depends on the DS of carboxyl groups and the concentration of CMS. Maximum cross-linking observed with CMS of DS, 0.49, and 50% (w/w) concentration demonstrates that the increased DS and concentration of CMS are favorable for cross-linking of CMS.